Collaborative Model Of Equality And Skills Program In An Effort To Empower Citizens To Learn Package B - Sutangsa (Eduscape : Journal of Education Insight, 2023)
The PKBM Bina Mandiri Cipageran package B equality education program has a superior program, namely the skills program. This business is a form of empowerment process for young people who are the forerunners of the nation's successors, especially in the demographic bonus era which requires young people to have competence as capital in the world of business and the world of work. The research we discuss is more about how to manage skills programs combined with package B equality education programs. The research method we use is qualitative using observation, interview and documentation study data collection techniques. From the research results, we found that the integration of equality and skills programs lies in the management of program components.